Based on two coconut (Cocos nucifera L.) genome-wide investigation of NODULE-INCEPTION-like protein family: evolution and expression profiles during development and stress - Li, Yubin; Li, Yujie; Hai, Xue; Bao, Cici; Zhao, Jinyang; Wang, Shouchuang; Zhou, Xianming; Liu, Penghui; Si, Chengcheng (Frontiers in Plant Science, 2025)
NODULE-INCEPTION-Like Protein (NLP) is a plant-specific transcription factor that plays a crucial role in nitrate uptake and stress responses. However, studies of NLP gene family in coconut are lacking. In this study, 7 NLP genes in the Aromatic Dwarf and 6 NLP genes in Hainan Tall coconut varities were identified. Furthermore, protein interaction network analysis suggested that CnD-NLP3/4/5 and CnT-NLP3/4/5 potentially interact with NRG2, HRS1, and LBD37, which may significantly influence nitrogen utilization in coconut, analysis of the promoters of CnD-NLPs and CnT-NLPs revealed many cis-acting elements associated with abiotic stress responses. Additionally, expression profiling showed that CnD-NLPs and CnT-NLPs were mainly expressed in mature leaves. Moreover, qRT-PCR analysis demonstrated that all identified CnD-NLPs responded to nitrogen deficiency, drought, and salt stress. Specifically, CnD-NLP5 may be a potentially critical gene in nitrogen deficiency responses, CnD-NLP4/5/6 and CnD-NLP1 may play a pivotal role in drought and salt stress response, respectively. And screening of homologous genes showed that CnD-NLP5 and AtNLP8, CnD-NLP4 and AtNLP7, CnD-NLP1 and OsNLP2 are homologous genes, with similar functions, further supporting their involvement in nitrogen deficiency, drought, and salt stress responses. These results lay the foundation for future research on the NLPs function and potential applications in coconut.